Varying Amplitude Vibration Phase Suppression Algorithm in ISAL Imaging - Hongfei Yin; Liang Guo; Yachao Li; Liang Han; Mengdao Xing; Xiaodong Zeng (Remote Sensing, 2022)
Platform vibration introduces sinusoidal modulation in inverse synthetic aperture lidar (ISAL) imaging, which causes paired echoes in ISAL imaging. In this paper, a varying amplitude vibration phase suppression algorithm is proposed. Working without prior knowledge, the proposed algorithm can suppress paired echoes under the condition of varying vibration amplitude and will not introduce new phase errors. Furthermore, the method is suitable for the imaging scene without isolated points. Both the simulated and real experiment results of ISAL turntable data demonstrate the effectiveness of the proposed algorithm.